Isosporiasis in a tertiary care center of North India - Neha Gautam; Sumeeta Khurana; Aman Sharma; Rakesh Sehgal (Wolters Kluwer Medknow Publications, 2014)
Background: Cystoisospora (Isospora) belli is a coccidian, protozoan parasite that resides in the gastrointestinal tract of humans. It is mainly reported from HIV-positive individuals. However, a few cases have been reported in other immunosuppressed individuals including renal transplant patients, and those with lymphoma and leukemia. Materials and Methods: During a period of 5 years (2008-2012), approximately 1700 stool samples of immunosuppressed patients were screened for the presence of opportunistic parasitic infections by a modified acid fast staining technique. Results: A total of 41 C. belli were reported, out of which 30 were HIV-positive individuals while 11 were HIV negative. The latter individuals were also immunosuppressed due to prolonged use of steroids or other immunosuppressive drugs. Twenty-six out of 30 HIV-positive patients and all the HIV-negative individuals with C. belli infection had diarrhea. Conclusion: All immunosuppressed individuals should be examined for the presence of opportunistic coccidian parasitic infections and treated accordingly and alternatively, isolation of opportunistic parasites should trigger a hunt for immunocompromised state to reduce the morbidity and mortality in such patients.